2023
DOI: 10.3389/fcell.2023.1091438
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral varicocele leads to ferroptosis, pyroptosis and necroptosis of human spermatozoa and affects semen quality in infertile men

Abstract: Purpose: This study explored the effects of bilateral varicocele on male semen quality in infertile men and the molecular mechanisms involving ferroptosis, pyroptosis and necroptosis signaling pathways.Methods: Totally, 20 healthy males and 26 patients with bilateral varicocele receiving infertility treatment were enrolled. Semen samples were collected. Basic semen parameters, acrosome integrity and membrane integrity, mitochondrial membrane potential (MMP) and apoptosis rate were compared. Levels of reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The bilateral nature of varicoceles can be elucidated by examining the venous anastomotic channel connecting the left and right gonadal veins. [9,20]. Moreover, the lack of valves in the gonadal veins is seen as a contributing factor to varicocele being a bilateral condition.…”
Section: Resultsmentioning
confidence: 99%
“…The bilateral nature of varicoceles can be elucidated by examining the venous anastomotic channel connecting the left and right gonadal veins. [9,20]. Moreover, the lack of valves in the gonadal veins is seen as a contributing factor to varicocele being a bilateral condition.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests a complementary relationship between the different pathways causing ferroptosis. Besides this, bilateral varicocele causes ferroptosis of human spermatozoa and affects semen quality in males with infertility [ 60 ]. In the future, whether fertility males accompanying testis or sperm ferroptosis will be worth exploring.…”
Section: Discussionmentioning
confidence: 99%
“…15 Another study revealed that semen quality was reduced in bilateral varicocele and that activating RIPK1, RIPK3, and HSP 90 was effective. 27 A study it was shown that SnS2 nanoflowers increased the necroptosis-related RIPK1-RIPK3-MLKL signal in testicular tissue by inducing oxidative stress. 28 As in these studies, RIPK1 activation, which we detected in our study, may adversely affect sperm quality and number motility.…”
Section: Discussionmentioning
confidence: 99%